Phenological mismatches and the demography of solitary bees - Vazquez, Diego P. (2023)
Species respond idiosyncratically to environmental variation, which may generate phenological mismatches. We assess the consequences of such mismatches for solitary bees. During 9 years, we studied flowering phenology and nesting phenology and demography of five wood-nesting solitary bee species representing a broad gradient of specialization/generalization in the use of floral resources. We found that the reproductive performance and population growth rate of bees tended to be lower with increasing nesting-flowering mismatches, except for the most generalized bee species. Our findings help elucidate the role of phenological mismatches for the demography of wild pollinators, which perform key ecosystem functions and provide important services for humanity. Furthermore, if climate change increases phenological mismatches in this system, we expect negative consequences of climate change for specialist bees.